Demystification and near-perfect estimation of minimum gas limit and gas used for Ethereum smart contracts - Danilo Rafael de Lima Cabral; Pedro Antonino; Augusto Cezar Alves Sampaio (Journal of Cloud Computing: Advances, Systems and Applications)
Abstract The Ethereum blockchain has a gas system that associates operations with a cost in gas units. Two central concepts of this system are the gas limit assigned by the issuer of a transaction and the gas used by a transaction. The former is a budget that must not be exhausted before the completion of the transaction execution; otherwise, the execution fails. Therefore, it seems rather essential to determine the minimum gas limit that ensures the execution of a transaction will not abort due to the lack of gas. Despite its practical relevance, this concept has not been properly addressed. In the literature, gas used and minimum gas limit are conflated. This paper proposes a precise notion of minimum gas limit and how it can differ from gas used by a transaction; this is also demonstrated with a quantitative study on real transactions of the Ethereum blockchain. Another significant contribution is the proposition of a fairly precise estimator for each of the two metrics. Again, the confusion between these concepts has led to the creation of estimators only for the gas used by a transaction. We demonstrate that the minimum gas limit for the state of the Ethereum blockchain (after the block) B can serve as a near-perfect estimation for the execution of the transaction at block $$B + Δ$$ , where $$Δ \le 11$$ ; the same holds for estimating gas used. These precise estimators can be very valuable in helping the users predict the gas budget of transactions and developers in optimising their smart contracts; over and underestimating gas used and minimum gas limit can lead to a number of practical issues. Overall, this paper serves as an important reference for blockchain developers and users as to how the gas system really works.